Historicity and Contextualization to The Problems of Moslem and Non-Moslem (A Hadith Study) - Ja`far Assagaf (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
Specifications of this paper are to discuss on the most traditions of the Prophet Muhammad pbuh about problematic social interactions of Moslems and Non-Moslems in the context of history and understanding which are implied inside it. The first is about greeting, congratulations for the great day. Secondly, Non-Moslems enter the mosque. The third is about eating meat of animals which are cut by Non-Moslems. All of these Specifications are often taking place with high intensity between Moslems and Non-Moslems in daily life. The problems of the relationship between Moslems and Non-Moslems are actual to be discussed. The issues are not infrequently to be in confinement the radical attitude of Moslems because of the understanding of religious texts, in this regard is the Qur'an, and hadith textually. The textually understandings of religious texts are combat command, killing, and dicriminating Non-Moslems. While, Non-Moslem communities do not try to learn on both the text histories from source Moslems deeply. Therefore, they have priori attitude towards certain clans. If they, especially for Moslems, are willing to learn aspects of religious texts comprehensively, so that, radical, and hostile attitude of Non-Moslem communities are nothing.